Comparative study of ambulatory blood pressure monitoring in hemodialysis and non-dialysis CKD patients and their prognostic value - Kumar, S. Senthil; Vithiavathi, S.; Doraickannu, T. (International Journal of Advances in Medicine, 2019)
Background: Hypertension and chronic kidney disease are inextricably intertwined. Most patients with hypertension associated CKD die of heart attack and stroke before renal function. Ambulatory BP monitoring provides automated measurements of BP during a 24hrs period while patients engaged in their usual activities including sleep. Recommended normal value include an average daytime BP <135/85mmHg/night time BP <120/70mmHg and 24 hr BP <130/89mmHg. In patients with chronic kidney disease the control of hypertension slows the progression of end stage renal disease. This study was undertaken to define the prognostic role of ABPM in dialysis dependent and non-dialysis CKD patients so that better treatment strategies could be initiated to prevent adverse outcomes. Methods: This prospective cross sectional study was conducted at Aarupadai Veedu Medical College and hospital, Puducherry in both dialysis dependent and non-dialysis CKD patients admitted in both ICU and medical wards. APBM was performed by using the properly validated ambulatory blood pressure monitor. The monitor records BP on the non-dominant arm every 20 minutes while awake and hourly while sleep for a total duration 24hrs in both hemodialysis dependent and non-hemodialysis patients. In hemodialysis dependent patients ABPM was recorded on the second day of hemodialysis. Results: The mean maximum systolic blood pressure in dialysis dependent and non-dialysis CKD patients recorded was 146.23 and 166.12 mmHg respectively. The mean minimum systolic blood pressure in dialysis dependent and non-dialysis CKD patients recorded was 122.11 and 122.45 mmHg respectively. The mean maximum diastolic blood pressure in dialysis dependent and non-dialysis CKD patients recorded was 100.24 and 110.65mmHg respectively. The mean minimum diastolic blood pressure in dialysis dependent and non-dialysis CKD patients recorded was 78.65 and 80.67 mmHg respectively. In our study the prevalence of non-dipping in dialysis and non-dialysis CKD patients were 28% and 16% respectively. Conclusions: Ambulatory blood pressure monitoring is considered the gold standard for the diagnosis of hypertension. Tight BP control is needed to limit the progression of renal disease and lessen cardiovascular morbidity and mortality. To achieve this goal ABPM should be widely adopted in patients with CKD.